Rapid, Multiplexed Characterization of Shiga Toxin-Producing Escherichia coli (STEC) Isolates Using Suspension Array Technology - Carter, John M.; Lin, Andrew; Clotilde, Laurie; Lesho, Matthew (Frontiers in Microbiology, 2016)
Molecular methods have emerged as the most reliable techniques to detect and characterize pathogenic Escherichia coli. These molecular techniques include conventional single analyte and multiplex PCR, PCR followed by microarray detection, pulsed-field gel electrophoresis (PFGE), and whole genome sequencing. The choice of methods used depends upon the specific needs of the particular study. One versatile method involves detecting serogroup-specific markers by hybridization or binding to encoded microbeads in a suspension array. This molecular serotyping method has been developed and adopted for investigating E. coli outbreaks. The major advantages of this technique are the ability to simultaneously serotype E. coli and detect the presence of virulence and pathogenicity markers. Here, we describe the development of a family of multiplex molecular serotyping methods for Shiga toxin-producing E. coli (STEC), compare their performance to traditional serotyping methods, and discuss the cost-benefit balance of these methods in the context of various food safety objectives.